2010
DOI: 10.1016/j.ejvs.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wall Stress on AAA Growth and Biomarkers

Abstract: Although lower relative wall stress was associated to a lower AAA growth rate, no relation was found between biomarker concentrations and wall stress. Future research may focus on more and extensive biomarker measurements in relation to AAA wall stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 24 publications
0
38
1
1
Order By: Relevance
“…Significant correlations with expansion were found in 2 studies (1 low and 1 medium bias risk; r =0.55 and r =0.42) with 61 follow‐up patients in total,10, 39 whereas 2 studies (1 low and 1 medium bias risk) could not reproduce such significant correlations in 66 follow‐up patients 18, 40. Pulinx et al, however, did reach significance when initial AAA diameter was included in their multivariate model 40…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Significant correlations with expansion were found in 2 studies (1 low and 1 medium bias risk; r =0.55 and r =0.42) with 61 follow‐up patients in total,10, 39 whereas 2 studies (1 low and 1 medium bias risk) could not reproduce such significant correlations in 66 follow‐up patients 18, 40. Pulinx et al, however, did reach significance when initial AAA diameter was included in their multivariate model 40…”
Section: Resultsmentioning
confidence: 88%
“…Complement reactive protein was examined as marker for expansion in 5 studies17, 18, 19, 20, 21 and in 2 as marker for rupture 22, 23. De Haro et al and Wiernicki et al were the only groups to demonstrate significant correlations with expansion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 illustrate some of the marker investigated for the association with small AAA growth. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Of the marker examined, only 2, namely D-dimer and plasmin-antiplasmin complex, have been associated with AAA growth after adjusting for initial AAA diameter in at least 2 distinct studies ( Table 1). [55][56][57] In the largest of these studies, in which 299 patients with small AAAs were included, it was reported that the use of plasma D-dimer plus initial aortic diameter enable the identification of groups of patients with AAA growth as disparate as 0.4 and 2.5 mm/y.…”
Section: Current Research To Identify Circulating Markers Of Aaa Progmentioning
confidence: 99%
“…Since the work of Vorp and others, who found that mechanical properties and stress are important factors in AAA rupture, many researchers have worked toward a non-invasive, clinical method to determine patient-specific aortic mechanical metrics (Doyle et al 2009, 2014; Fillinger et al 2003; Helderman et al 2008; Li et al 2008; Raghavan et al 2000; Speelman et al 2010; Vorp et al 1998; Wang et al 2002). US elastography techniques offer a clinically accessible tool for potentially providing these metrics.…”
Section: Discussionmentioning
confidence: 99%